Investigation of two-phase flow behavior and patterns in horizontal and vertical pipe / Mohamad Ardan Zubir - Mohamad Ardan , Zubir (2015)
Two-phase flow takes place in a wide range of application in the industry. Basic research related to two-phase flow such as flow pattern and void fraction is very useful in contributing to design for optimized the system. This research analyzed the behavior and pattern of the two-phase air- water flow in the pipes. The relationships of the pipe diameter with the flow behavior and the aspect ratio, L/D of the pipe are examined. Three different pipes sizes of 21.0-mm, 47.0-mm and 95.0-mm inner diameters with length of 3 meter are used in this experiment. The flows are upward vertically positioned and horizontal which are supported by a steel frame and a close loop water system. The superficial velocities for the air and water flow are set between 0.02 to 2.0 m/s for air, and 0.02 to 3.0 m/s for water, depending on the size of the pipe. A high speed video camera is utilized to capture the flow patterns for different pipe orientations and flow velocities. All data were analyzed, tabulated and displayed in form of figures and graphs. The study continues by developing a measurement method to calculate the void fraction. A simple conductance probe device is designed using a ring shape sensor connected to the LABView data acquisition device. The result of the void fraction measurement in two-phase flow than compared with other related correlation. The diameter size and aspect ratio L/D of the pipes has significant impact on the flow patterns.